The system functions of direct democracy - a ranking of 103 countries in the world - Hornig, Eike-Christian; Frommelt, Christian (Frontiers in Political Science, 2024)
We introduce a new framework of the functions of direct democracy within democratic political system. These are: ( 1countries around the world, we find that the input and exit functions are rather unbalanced in their dynamics. The exit function shows a tendency to strengthen the concentration of power, whereas the input function rarely allows for access to both decision-making arenas. But once issues reach the referendum, the impact is often strong and only a small minority of states conduct referendums without any formal consequences. Beyond these results, the presented approach allows to start longtime observations of the state of direct democracy in democratic systems.